Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1002/cne.21063
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal development and gender‐dependent expression of TIP39 in the rat brain

Abstract: Tuberoinfundibular peptide of 39 residues (TIP39) is a selective agonist of the parathyroid hormone 2 (PTH2) receptor. The topographical distributions of TIP39 and the PTH2 receptor in the brain, described in young male rats, suggested that TIP39 has limbic and endocrine functions. In the present study, we investigated the expression of TIP39 and the PTH2 receptor in male and female rat brain during postnatal development by means of in situ hybridization histochemistry, quantitative RT-PCR and immunocytochemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 50 publications
(80 reference statements)
5
31
0
Order By: Relevance
“…Thus, while other neuronal inputs to the galanin neurons may also convey information about pup interaction, TIP39 terminals are likely to play an important role in this process. TIP39 itself may modulate the synaptic information transfer as the receptor for TIP39, parathyroid hormone 2 receptor (PTH2R) is abundant in the preoptic area (Dobolyi et al 2006a, b). Since the PTH2R is also excitatory (Dobolyi et al 2010), we conclude that the activity of galanin neurons is likely increased by the input from the PIL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, while other neuronal inputs to the galanin neurons may also convey information about pup interaction, TIP39 terminals are likely to play an important role in this process. TIP39 itself may modulate the synaptic information transfer as the receptor for TIP39, parathyroid hormone 2 receptor (PTH2R) is abundant in the preoptic area (Dobolyi et al 2006a, b). Since the PTH2R is also excitatory (Dobolyi et al 2010), we conclude that the activity of galanin neurons is likely increased by the input from the PIL.…”
Section: Discussionmentioning
confidence: 99%
“…Every fourth free-floating section was first stained for TIP39 using FITC-tyramide amplification fluorescent immunocytochemistry. An affinity-purified antiserum from a rabbit immunized with rat TIP39, which can be absorbed with synthetic TIP39 (Dobolyi et al 2002), and labels cell bodies with the same distribution as observed by in situ hybridization histochemistry (Dobolyi et al 2006a, b), was used as primary antiserum. This antiserum (1:3000) was applied for 48 h at room temperature, followed by incubation of the sections in biotinylated donkey anti-rabbit secondary antibody (1:1000; Jackson ImmunoResearch), then in ABC complex (1:500; Vector Laboratories) for 2 h. Sections were subsequently incubated with FITC-tyramide (1:8000) and H 2 O 2 in Tris hydrochloride buffer (0.1 M, pH 8.0) for 6 min.…”
Section: Methodsmentioning
confidence: 99%
“…The relatively few TIP39-expressing neurons in the parvicellular (lateral) subparafascicular nucleus and the posterior intralaminar thalamic nucleus in the adult and young rats was previously considered a lateral extension of the subparafascicular area Dobolyi et al, 2006b;Wang et al, 2006b) because the density of TIP39-expressing neurons was higher medially around the magnocellular subparafascicular nucleus and because some TIP39 neurons were continuously distributed laterally in the direction of the posterior intralaminar thalamic nucleus. The significant expression of TIP39 in and around the posterior intralaminar thalamic nucleus during embryonic development changes this view.…”
Section: Correspondence With Postnatal Development Of Tip39mentioning
confidence: 98%
“…TIP39 was detected with an affinity-purified antiserum from a rabbit immunized with rat TIP39 which can be absorbed with synthetic TIP39 (Dobolyi et al 2002, 2003b) and labels cell bodies with the same distribution as observed by in situ hybridization histochemistry (Dobolyi et al 2003b, 2006). This antiserum (1:3,000) was applied for 48 h at room temperature followed by incubation of the sections in biotinylated anti-rabbit secondary antibody (1:800 dilution; Vector Laboratories, Burlingame, CA, USA) and then in avidin–biotin-peroxidase complex (1:300; Vector Laboratories, Burlingame, CA, USA) for 2 h. Subsequently, sections were treated with fluorescein isothiocyanate (FITC)-tyramide (1:8,000) and H 2 O 2 in Tris–hydrochloride buffer (0.1 M, pH 8.0) for 6 min, mounted on positively charged slides (Superfrost Plus, Fisher Scientific, Pittsburgh, PA, USA) and coverslipped in antifade medium (Prolong Antifade Kit, Molecular Probes, Eugene, OR, USA).…”
Section: Methodsmentioning
confidence: 95%
“…After diluting RNA to 2 μg/μl, it was treated with Amplification Grade DNase I (Invitrogen) and cDNA was synthesized with a Superscript II reverse transcriptase kit (Invitrogen) according to the manufacturer’s instructions. After tenfold dilution, 2.5 μl of the resulting cDNA was used as template in multiplex PCR reactions using dual-fluorescence labeled TAQMAN probes for TIP 39 (6-FAM-CGCTAGCTGACGACGCGGCCT-TAMRA), and glyceraldehyde-3-phosphate-dehydrogenase (GAPDH; JOE-ATGGCCTTCCGTGTTCCTACCCCC-TAMRA) as described previously (Dobolyi et al 2006). The primers for TIP39 (CTGCCTCAGGTGTTGCCCT and TGTAAGA GTCCAGCCAGCGG) were used at 300 nM whereas the primers for GAPDH (CTGAACGGGAAGCTCACTGG and CGGCATGTCAGATCCACAAC) were used at 150 nM concentration.…”
Section: Methodsmentioning
confidence: 99%